2022
DOI: 10.3389/fimmu.2021.752888
|View full text |Cite
|
Sign up to set email alerts
|

CD1dhiPD-L1hiCD27+ Regulatory Natural Killer Subset Suppresses Atopic Dermatitis

Abstract: Effector and regulatory functions of various leukocytes in allergic diseases have been well reported. Although the role of conventional natural killer (NK) cells has been established, information on its regulatory phenotype and function are very limited. Therefore, the objective of this study was to investigate the phenotype and inhibitory functions of transforming growth factor (TGF)-β-producing regulatory NK (NKreg) subset in mice with MC903-induced atopic dermatitis (AD). Interestingly, the population of TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
(98 reference statements)
1
4
0
Order By: Relevance
“…2DS4*001:01 and 2DL4*001:02 in the presence of C*04:01 and the KIR B haplotype 2DL4*001:02$2DS4*001:01$3DL2:002:01 also in the presence of C*04:01 is associated with decreased likelihood for AD remission (i.e., severe AD). This is likely consistent with the findings of both Mack et al and Min et al, who indicated that the activation of circulating NK cells appears to decrease AD symptoms (7,56). This is also consistent with a recent study by M€ obus et al, who showed that NK cell numbers were elevated in AD lesion and nonlesion skin and that NK cell activation by successful treatment results in clinical improvement (52,57).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…2DS4*001:01 and 2DL4*001:02 in the presence of C*04:01 and the KIR B haplotype 2DL4*001:02$2DS4*001:01$3DL2:002:01 also in the presence of C*04:01 is associated with decreased likelihood for AD remission (i.e., severe AD). This is likely consistent with the findings of both Mack et al and Min et al, who indicated that the activation of circulating NK cells appears to decrease AD symptoms (7,56). This is also consistent with a recent study by M€ obus et al, who showed that NK cell numbers were elevated in AD lesion and nonlesion skin and that NK cell activation by successful treatment results in clinical improvement (52,57).…”
Section: Discussionsupporting
confidence: 89%
“…A more recent study by Mack et al revealed that the number of circulating NK cells in adults with moderate to severe AD was significantly less than in a healthy control population (7). This was recently replicated (16,56). Mack et al further noticed a diminished number of circulating mature NK cells, whereas lesional AD skin was enriched for activated NK cells (7).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In details, they found that the majority of cutaneous ILCs between AD and normal human skin (NHS) belonged to the CRTH2 + subpopulation and these cells resided in the upper skin layers [59]. Instead, Min verified that the CD1d hi PD-L1 hi CD27 + regulatory NK cell subset could efficiently suppress AD via significantly inhibiting the numbers of ILC2s and Th2 cells, which collectively suggested the biofunction and association of TGF-β-producing NK cells with the severity of AD [60].…”
Section: Natural Killer (Nk) Cellsmentioning
confidence: 99%